New clothing resistance scheme for estimating outdoor environmental thermal load - Ács, Ferenc; Kristóf, Erzsébet; Zsákai, Annamária (Geographica Pannonica, 2019)
A new clothing resistance model for estimating outdoor thermal load is proposed and its behavior is analyzed in different weather conditions. It is based on clothed human body energy balance considerations; the human treated is a walking human in outdoor conditions. Weather and human data are taken from the internet site of the Hungarian Meteorological Service and from a Hungarian human dataset, respectively. Environmental thermal load is characterized in terms of clothing resistance rcl and operative temperature. The model’s main strength is that it simulates metabolic rate M as simply as possible. rcl deviations caused by personal variations of M are the largest in extreme cold and warm conditions, in the comfort zone this effect is non-essential. rcl deviations caused by wind speed variations can be especially large in large heat excess cases. Further model tests are needed for more extreme conditions.